2021
DOI: 10.3389/fphar.2021.674520
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Guided Fractionation and Molecular Networking Reveal Fatty Acids to Be Principal Anti-Parasitic Compounds in Nordic Seaweeds

Abstract: Widespread use of antimicrobial drugs has led to high levels of drug-resistance in pathogen populations and a need for novel sources of anti-bacterial and anti-parasitic compounds. Macroalgae (seaweed) are potentially a rich source of bioactive compounds, and several species have traditionally been used as vermifuges. Here, we investigated the anti-parasitic properties of four common cold-water Nordic seaweeds; Palmaria palmata (Rhodophyta), Laminaria digitata, Saccharina latissima and Ascophyllum nodosum (Och… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Bonde et al . (2021) [ 32 ] for example, demonstrated the parasitic development inhibition effect of the extracts derived from the seaweed from the cold waters of the Nordic region. In addition, the presence of fatty acids, including stearidonic acid, alpha-linolenic acid, docosahexaenoic acid, arachidonic acid, and eicosapentaenoic acid, was demonstrated to promote anthelmintic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bonde et al . (2021) [ 32 ] for example, demonstrated the parasitic development inhibition effect of the extracts derived from the seaweed from the cold waters of the Nordic region. In addition, the presence of fatty acids, including stearidonic acid, alpha-linolenic acid, docosahexaenoic acid, arachidonic acid, and eicosapentaenoic acid, was demonstrated to promote anthelmintic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Still concerning the chemical composition of C. chinense peel and seeds, they contain several fatty acids that have great antifungal potential, including activity against Candida spp. [ 66 , 67 ]. Moreover, the antiparasitic potential of fatty acids has also been evidenced [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides SL, molecular networking analyses predicted significantly high bioactivity scores for flavonoid and fatty acid derivatives. Natural flavonoids have been extensively described to induce anti-protozoal activity against several trypanosomatid parasites ( Cockram and Smith, 2018 ; Izumi et al, 2011 ), whereas fatty acids were recently suggested to be involved in the anti-parasitic activity of seaweeds ( Bonde et al, 2021 ). Furthermore, in the present study the various not annotated compounds with high bioactivity scores likely contributed to the activity of the tested purified extracts, either as single compounds or in combination with other metabolites.…”
Section: Discussionmentioning
confidence: 99%